Programmed cell death suppression in transformed plant tissue by tomato cDNAs identified from an Agrobacterium rhizogenes-based functional screen - Harvey, Jagger J.W.; Lincoln, J.E.; Gilchrist, D.G. (Springer, 2008)
The genetic regulation of programmed cell death (PCD) is well characterized in animal systems, but largely unresolved in plants. This research was designed to identify plant genes that can suppress PCD triggered in plants by Fumonisin B1 (FB1). Agrobacterium rhizogenes was used to transform individual members of a cDNA library into tomato roots, which were then screened for resistance to FB1. Cellular changes elicited during FB1-induced PCD include chromatin condensation, fragmentation into pycnotic DNA bodies, TUNEL positive reactions, ROS accumulation, and eventual loss of membrane integrity. Several cDNA library members collectively overexpressed in a transformed root population revealed PCD suppressive action and were recovered by PCR. One of the FB1 suppressive genes was homologous to metallothionein, and shared sequence homology to the animal ortholog reported to suppress PCD through interference with formation or activity of reactive oxygen species (ROS). The metallothionein recovered in this screen suppressed ROS accumulation in FB1-treated roots and prevented symptoms of PCD. Anti-PCD genes recovered by this screen represent potential sources of resistance to PCD-dependent plant diseases, while the screen should be useful to identify genes capable of suppressing PCD triggered by other effectors, including those expressed by root pathogens during infection.